CGIAR Report to the Nineteenth Regular Session of the Commission on Genetic Resources for Food and Agriculture - CGIAR (2023)
This report was prepared by CGIAR in response to an invitation from the Secretariat of the FAO Commission on Genetic Resources for Food and Agriculture. It is structured to correspond, in general, to agenda items 2-11 of the Nineteenth Regular Session of the Commission on Genetic Resources for Food and Agriculture (CGRFA-19). Some sections of this report were previously included in the CGIAR submission to the Eleventh Session of the Intergovernmental Technical Working Group on Plant Genetic Resources (ITWG-PGRFA-11), in April 2023.